ANALISIS KELAYAKAN EKONOMI PADA HOME INDUSTRY PEMBUATAN KERUPUK - Israhmandika, - (2019)
One of the problems that often arise for business actors is the weakness of economic feasibility analysis of the business. Large-scale white crackers are the least demanding shelves type of crackers. It is therefore necessary to analyze whether large-scale white crackers production is feasible or not to be produced especially in terms of economic aspects. Purpose of the research is to provide a proposal by conducting a feasibility analysis the ecomomic of Home Industry to make crackers. The methods used to measure feasibility analysis are NPV (Net Present Value), BCR (Benefit Cost Ratio), IRR (Internal Rate of Return), PI (Profitability Index), BEP (Break Even Point) and sensitivity analysis. And provide suggestions by measuring and analyzing the investment level of large-scale white crackers production in the scope of technical economics. From the calculation of business feasibility analysis obtained Net Present Value (NPV) is Rp 246.501.026, -. The Break Even Point (BEP) consists of BEP units and BEP rupiah, BEP units of 2596 units and BEP rupiah of Rp 1.167.975.387, -, Internal Rate of Return (IRR) is 24,10% to 24,20%. Benefit Cost Ratio (BCR) of 1,0384. Profitability Index (PI) of 1,2969. From the calculation results can be said that the production of large-scale white crackers deserve to be produced. Sensitivity analysis of the decline in selling prices, more than 3% is not feasible. For sensitivity analysis, raw material price increase of more than 14% is not feasible. Thus, it can be said that the price of large-scale white cracker products is very sensitive